The history of the civil war in Tajikistan - Bashiri, Iraj (Central Asian studies, 2020)
"The book is about the Tajiks, a Muslim community in Central Asia, their Sovietization, and their bloody civil war. The conflict was about the type of constitution that Tajikistan should adopt: Communist, secular, or based on the Islamic Shari'a. The parliamentary discussions aimed at preventing a war, and the armed struggle that ensued are both discussed in detail. Events are seen through the eyes of Safarali Kenjaev, Chairman of the Supreme Soviet of Tajikistan at the time. The volume also includes the author's impressions and interviews gathered during his year-long residence (1993) in war-torn Tajikistan as IREX's man in Dushanbe."--